CONTENT, FORM, METHOD AND MEANS OF TEACHING "INFORMATICS AND INFORMATION TECHNOLOGIES" USING MEDIA TECHNOLOGIES - Sulaymanova Dildora Bakhtiorovna (Scholar Express Journals, 2022)
Organization of the teaching process of informatics and information technologies on the basis of media technologies is presented
Keywords: Media technology; media education; resource; form